2010
DOI: 10.1007/s00234-010-0714-5
|View full text |Cite
|
Sign up to set email alerts
|

MTR variations in normal adult brain structures using balanced steady-state free precession

Abstract: Introduction Magnetization transfer (MT) is sensitive to the macromolecular environment of water protons and thereby provides information not obtainable from conventional magnetic resonance imaging (MRI). Compared to standard methods, MT-sensitized balanced steady-state free precession (bSSFP) offers high-resolution images with significantly reduced acquisition times. In this study, high-resolution magnetization transfer ratio (MTR) images from normal appearing brain structures were acquired with bSSFP. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…The homogeneous MT values (MTR and qMT) obtained with the bSSFP method in the ref ROIs corresponded to those known from the literature arguing for the reproducibility of the data. In general, MTR values within the lesions showed the same tendencies as F and kf with opposite tendencies for T1 and T2 (Tables and ), according to findings from qMT analysis in patients with MS and ischemia…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The homogeneous MT values (MTR and qMT) obtained with the bSSFP method in the ref ROIs corresponded to those known from the literature arguing for the reproducibility of the data. In general, MTR values within the lesions showed the same tendencies as F and kf with opposite tendencies for T1 and T2 (Tables and ), according to findings from qMT analysis in patients with MS and ischemia…”
Section: Discussionsupporting
confidence: 80%
“…The drawback of low resolution has been addressed by a novel MT‐sensitized method using balanced steady‐state free precession (bSSFP), providing whole brain isotropic MTR and qMT parameter maps, which, however, until recently still required TAs of about 30 minutes. The advantages of MT imaging (MTR and qMT) with bSSFP over common spoiled gradient echo (SPGR) sequences, has previously been analyzed in normal brain structures . In general, qMT parameters obtained with bSSFP were in good accordance with prior studies and, in contrast to studies using SPGR sequences for MT assessment, the bSSFP method allowed the analysis of even small brain structures due to its high resolution and provided a higher signal‐to‐noise ratio.…”
Section: Background and Purposementioning
confidence: 63%
“…In this respect recent advances based on the balanced SSFP sequence hold promise. For instance this approach has been shown to be a robust, sensitive and very fast measure of MTR which generates values that are comparable across multiple measurement sites [7,18,19]. In the present study, we therefore chose to include the fast balanced SSFP MT method as an integral part of our white matter protocol.…”
Section: Discussionmentioning
confidence: 99%
“…in WM disorders [4,17]. In the present study, the fast bSSFP MT method is used, which has been shown to be a robust, sensitive and very fast measure of MTR [7,18,19]. …”
Section: Introductionmentioning
confidence: 99%
“…4 ms) is the same as the average of the short and long TRs of the on-resonance method (e.g. 3 ms and 5 ms [ 24 ]), the time for actual data acquisition will be similar between the two methods, except for the interslice delay required by the interslice method. Data from a single subject ( Fig.…”
Section: Discussionmentioning
confidence: 99%